Narrative Review of the Relationship Between CKD and Diabetic Foot Ulcer - Bonnet, Jean-Baptiste; Sultan, Ariane (Kidney international reports, 2022)
Diabetic foot ulcer (DFU) and chronic kidney disease (CKD) are 2 significant complications of diabetes mellitus (DM). Up to 40% of patients with DM are expected to also develop CKD, and 19% to 34% will suffer from DFU during their lifetimes. However, data on the link between podiatric risk and the extent of CKD are scarce. Neuropathy, a key element of the International Working Group on the Diabetic Foot (IWGDF) classification, nevertheless appears to be related to the CKD stage. The incidence of DFU and its poor evolution also appear to be linked to the stage of CKD, with mortality reaching its peak in patients with end-stage renal disease (ESRD). Whatever, the decrease in the rate of diabetic foot amputation observed worldwide, especially for major amputations, is also observed in patients with ESRD. Specific actions taken for patients undergoing dialysis seems to improve the DFU prognosis. CKD and DFU share a number of elements of pathophysiology, the first of which is peripheral arterial disease (PAD). Uremic neuropathy and nutritional status also seem to create a link between the development of the 2 complications. This literature review provides an update on the complex and dynamic relationship between DFU and CKD. It examines the epidemiologic link between CKD and diabetic foot risk, CKD and DFU occurrence, and CKD and DFU prognosis. It focuses on the pathophysiological links between these 2 complications. Finally, it highlights the actions taken to improve management in the ESRD population that have reduced the rate of major amputations in this population by more than half.